Possible causes inhibiting the purchase of Chinese grocery own brands: a preliminary study - Song, Wei (Journal of Business Economics and Management, 2012)
The aim of this preliminary study is to identify the possible causes inhibiting consumers from purchasing Chinese own brands. In view of the absence of literature on this aspect of commerce in Asia, a review of Western literature was conducted. The data for this study is from semi-structured in-depth interviews with Chinese retail consultants and grocery shoppers in Shanghai, China. The results of the study show that negative low price image, low perceived own brand quality, and the importance of “face” in Chinese culture are the key factors resulting in negative sentiment toward Chinese grocery own brands. The results of this investigation are expected to provide a basis for making recommendations for the use of both international and Chinese retailers when building Chinese grocery own brands. The findings of this study have been generated from a small group of interviewees in a single city and thus cannot be considered conclusive. Therefore further research in other cities of China and other Asian countries should be conducted. The study offers novel views from the consumer perspective on the unwillingness to buy own brands in emerging markets.